Partisipasi Anggota Dan Kemampuan Manajerial Pengurus Implikasinya Terhadap Pengembangan Usaha Koperasi Berbasis Syariah - Harkit Rahmawati (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2018)
The number of cooperative corporations that experienced business failure, in 2014 as many as 72,230 cooperatives or about 35% of the total 260 thousand cooperatives went bankrupt. A different phenomenon emerged in Sharia-based financial institutions, since it was first introduced in 1990, there are only a few dozen units, and at present the number in Indonesia is over 5,500. According to Ropke 'the success of a Cooperative is influenced by internal factors (Managers (Managers and managers), Service, Member Participation, and Capital) and external factors (Business climate (competition) and Government policy and technological developments). This research is conducted to know the extent of implication or influence of member participation and managerial capability of management toward syariah based business development. The method are used is descriptive analytic with Quantitative approach, The type of data in this study is the primary data sourced from the Board and Members of Sharia cooperatives in Purwakarta district. Data collection techniques conducted are interviews to administrators and observation data cooperatives development in terms of Capital, the number of Members, turnover, the rest of the business results (earnings) from the year 2010-2016. The results showed that member participation has a positive effect on the development of Sharia-based cooperatives with a significance level of 74.6%, While Managerial Ability has positive effect to Cooperative development equal to 56,3%. Simultaneously Member participation, and managerial ability have positive effect on Cooperative development equal to 57,67%.